Effectiveness of Intraoperative Parathyroid Monitoring (ioPTH) in predicting a multiglandular or malignant parathyroid disease. (May 2017) - Dobrinja, C.; Santandrea, G.; Giacca, M.; Stenner, Elisabetta; Ruscio, Maurizio; de Manzini, Nicolò
Abstract: Aim: The main goal of our study was to confirm the usefulness of intra-operative parathyroid hormone (PTH) monitoring (ioPTH) when using minimally invasive techniques for treatment of sporadic Primary hyperparathyroidism (pHTP). Furthermore, we aimed to evaluate if ioPTH monitoring may help to predict the etiology of primary hyperparathyroidism, especially in malignant or multiglandular parathyroid disease. Methods: A retrospective review of 125 consecutive patients with pHPT who underwent parathyroidectomy between 2001 and 2016 at the Department of General Surgery was performed. For each patient, the specific preoperative work-up consisted of: high-resolution US of the neck by a skilled sonographer, sestamibi parathyroid scan, laryngoscopy, and serum measurement of PTH, serum calcium levels, and serum 25(OH)D levels. Results: The study included 125 consecutive patients who underwent surgery for pHPT. At the histological examination, we registered 113 patients with simple adenomatous pathology (90, 4%), 5 atypical adenomas (4%), 3 cases of parathyroid carcinoma (2, 4%), , , and 4 histological exams of different nature (3, 2%). Overall, 6 cases (4, 8%) of multiglandular disease were found. We reported 10 cases (8%) of recurrent/persistent hyperparathyroidism: 1/10 in a patient affected by atypical adenoma, 9/10 in patients with benign pathology. Regarding these 10 cases, in three (30%) patients, ioPTH wasn't dosed (only frozen section (FS) exam was taken), in 5 cases (50%) ioPTH dropped more than 50% compared to basal value (false negative results), and in 2 (20%) cases, ioPTH did not drop >50% from the first samples taken, the extemporary exam had confirmed the presence of adenoma and the probable second hyperfunctioning adenoma was not found. Conclusions: IoPTH determinations ensure operative success of surgical resection in almost all hyperfunctioning tissue; in particular it is very important during minimally invasive parathyroidectomy, as it allows avoiding bilateral neck exploration. The use of ioPTH monitoring offer increased sensitivity in detecting multiglandular disease and can minimize the need and risk associated with recurrent operations, and may facilitate cost-effective minimally invasive surgery. Moreover, intraoperative PTH monitoring could be a reliable marker to predict a malignant disease during parathyroidectomy, showing higher ioPTH baseline value and superior drop compared to benign disease. Highlights: The best surgical approach for parathyroidectomy and the use of routine intraoperative parathyroid hormone (ioPTH) monitoring is still debated. ioPTH monitoring could be a reliable marker to predict a malignant disease during parathyroidectomy. In case of malignant parathyroid disease, ioPTH monitoring show higher ioPTH baseline value and superior drop compared to benign disease. There are no significant differences in ioPTH in atypical adenomas and in multiglandularular disease. ioPTH monitoring is able to reinforce indication for a minimal-invasive approach Accurate patient selection is important to achieve the best results.